SISTEM BIKAMERAL DI INDONESIA SEBAGAI FUNGSI LEGISLASI DEWAN PERWAKILAN DAERAH DITINJAU DARI PERSPEKTIF MASLAHAH - Amaluddin, Zainal (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2021)
The Legislative Function of the Regional Representative Council The bicameral structure, especially in Indonesia, is viewed from a maslahah perspective. This study aims to analyze: (1) What is the legislative function of the Regional Representative Council in the bicameral system in Indonesia after the enactment of Law No.17 of 2014 concerning MD3, (2) What is the legislative function of the Regional Representative Council when viewed from the Maslahah perspective. This research is a type of normative legal research using two approaches, namely legislation and history. The statutory approach aims to examine in depth the various regulations governing the legislative duties and functions of the DPD, while the historical approach is used to understand the parliamentary system in Indonesia. After the data has been collected, the data is analyzed using descriptive analysis method which aims to describe the object under study in order to get a comprehensive picture. Furthermore, the data is analyzed based on maslahah theory using deductive methods because it analyzes through reasoning from a general form to achieve a special form. The results showed that: the legislative authority of the DPD which was originally expanded by the Constitutional Court in its decision No. 92 / PUU-X / 2012 apparently were not accommodated in the formulation of Law No.17 of 2014, this is evident in the MD3 Law that still contains several articles that again narrow down the constitutional authority of the DPD. If viewed from the maslahah perspective, the legislative functions of the DPD and Ahlul halli wal 'aqd in the Islamic constitutional system are very different. Although both have the same authority, namely in the field of legislation, the authority of Ahlul halliwal 'aqd is clearer and not as clear as the DPD legislation, besides that the DPD has not been placed equal to the DPR and the President in exercising its authority as a legislative institution especially after the enactment of Law No. .17 of 2014.